Performance difficulties of Sharif Muhiyddin Haider’s musical works among Oud students (Al-Academy, 2017)
This research focuses on the difficulties that face Oud's students' in the performance of Sharif Muheyddin Haider musical works. In addition, this research suggests solutions to overcome these difficulties for make it easier to play Haider's musical works. This research also addressed important topics of great relevance the title, problem and the research's aims. Moreover, Procedures of this research adopted the descriptive approach (content analysis) to attain the research's aims. Furthermore, results and discussions where covered, and conclusions of the appropriate academic solutions were achieved to overcome the performance difficulties of Haider's musical works among Oud's students'. At the end, the research presents a set of recommendations and suggestions, and provides a list of sources and references.